A case report of classic galactosemia with a GALT gene variant and a literature review - Yong-cai Wang; Lian-cheng Lan; Xia Yang; Juan Xiao; Hai-xin Liu; Qing-wen Shan (BMC, 2024)
Abstract Background Galactosemia is an autosomal recessive disorder resulting from an enzyme defect in the galactose metabolic pathway. The most severe manifestation of classic galactosemia is caused by galactose-1-phosphate uridylyltransferase (GALT) deficiency, and this condition can be fatal during infancy if left untreated. It also may result in long-term complications in affected individuals. Case presentation This report describes a patient whose initial clinical symptoms were jaundice and liver dysfunction. The patient's liver and coagulation functions did not improve after multiple admissions and treatment with antibiotics, hepatoprotective and choleretic agents and blood transfusion. Genetic analysis revealed the presence of two variants in the GALT gene in the compound heterozygous state: c.377 + 2dup and c.368G > C (p.Arg123Pro). Currently, the variant locus (c.377 + 2dup) in the GALT gene has not been reported in the Human Gene Mutation Database (HGMD), while c.368G > C (p.Arg123Pro) has not been reported in the Genome Aggregation Database (GnomAD) nor the HGMD in East Asian population. We postulated that the two variants may contribute to the development of classical galactosemia. Conclusions Applications of whole-exome sequencing to detect the two variants can improve the detection and early diagnosis of classical galactosemia and, more specifically, may identify individuals who are compound heterozygous with variants in the GALT gene. Variants in the GALT gene have a potential therapeutic significance for classical galactosemia.